2023
DOI: 10.1186/s12859-023-05533-4
|View full text |Cite
|
Sign up to set email alerts
|

Picky with peakpicking: assessing chromatographic peak quality with simple metrics in metabolomics

William Kumler,
Bryna J. Hazelton,
Anitra E. Ingalls

Abstract: Background Chromatographic peakpicking continues to represent a significant bottleneck in automated LC–MS workflows. Uncontrolled false discovery rates and the lack of manually-calibrated quality metrics require researchers to visually evaluate individual peaks, requiring large amounts of time and breaking replicability. This problem is exacerbated in noisy environmental datasets and for novel separation methods such as hydrophilic interaction columns in metabolomics, creating a demand for a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…In each case, the differences introduced by SLA were smaller than those of depth when compared directly, with even the high-resolution sampling around the DCM finding slightly more variance explained by the 40 meter difference in sampling depth than the 40 centimeter difference in SLA. This result agrees well with prior research by Heal et al (2021) and Kumler et al (2023) showing the large effect of sampling depth on the metabolome.…”
Section: Multivariate Approaches Reveal Metabolome-wide Shifts Across...supporting
confidence: 93%
See 2 more Smart Citations
“…In each case, the differences introduced by SLA were smaller than those of depth when compared directly, with even the high-resolution sampling around the DCM finding slightly more variance explained by the 40 meter difference in sampling depth than the 40 centimeter difference in SLA. This result agrees well with prior research by Heal et al (2021) and Kumler et al (2023) showing the large effect of sampling depth on the metabolome.…”
Section: Multivariate Approaches Reveal Metabolome-wide Shifts Across...supporting
confidence: 93%
“…One notable aspect of their clustering was the way in which the deepest samples (DCM plus 20m) grouped most closely to the anticyclonic samples, perhaps indicating that below the DCM the metabolome rapidly approaches a uniform deep-water signal. This result was noted previously in the 175 meter samples of the eddy transect in Kumler et al (2023), where samples from the deep euphotic zone showed greater intradepth similarity than samples from the DCM or 25 meters.…”
Section: Multivariate Approaches Reveal Metabolome-wide Shifts Across...supporting
confidence: 86%
See 1 more Smart Citation